Validity of parent-reported weight and height of preschool children measured at home or estimated without home measurement: a validation study - Cox Bianca; De Keyzer Willem; De Vriendt Tineke; Ottevaere Charlene; Himes John H; Huybrechts Inge; Van Trimpont Inge; De Bacquer Dirk; De Henauw Stefaan (BMC, 2011)
Abstract Background Parental reports are often used in large-scale surveys to assess children's body mass index (BMI). Therefore, it is important to know to what extent these parental reports are valid and whether it makes a difference if the parents measured their children's weight and height at home or whether they simply estimated these values. The aim of this study is to compare the validity of parent-reported height, weight and BMI values of preschool children (3-7 y-old), when measured at home or estimated by parents without actual measurement. Methods The subjects were 297 Belgian preschool children (52.9% male). Participation rate was 73%. A questionnaire including questions about height and weight of the children was completed by the parents. Nurses measured height and weight following standardised procedures. International age- and sex-specific BMI cut-off values were employed to determine categories of weight status and obesity. Results On the group level, no important differences in accuracy of reported height, weight and BMI were identified between parent-measured or estimated values. However, for all 3 parameters, the correlations between parental reports and nurse measurements were higher in the group of children whose body dimensions were measured by the parents. Sensitivity for underweight and overweight/obesity were respectively 73% and 47% when parents measured their child's height and weight, and 55% and 47% when parents estimated values without measurement. Specificity for underweight and overweight/obesity were respectively 82% and 97% when parents measured the children, and 75% and 93% with parent estimations. Conclusions Diagnostic measures were more accurate when parents measured their child's weight and height at home than when those dimensions were based on parental judgements. When parent-reported data on an individual level is used, the accuracy could be improved by encouraging the parents to measure weight and height of their children at home.